PELAKSANAAN PELEPASAN HAK ATAS TANAH ADAT SUKU WORIASI DI KABUPATEN KEPULAUAN YAPEN PROVINSI PAPUA SEBAGAI SYARAT PEMBERIAN HAK GUNA BANGUNAN PADA BADAN HUKUM PT. SINAR WIJAYA PLYWOOD INDUSTRIES DALAM KONTEKS KEPASTIAN HUKUM - Rizki Hirmanto; Mella Ismelina F.R. (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2021)
Land registration is regulated by the Basic Agrarian Law Article 29 (UUPA) also Government Regulation Number 24 of 1997 about land registration that has a purpose to give guarantee of legal certainty of land. Alongs with the use of Indonesia land increasingly to remote areas, the businessmen that need land as the business facility such as PT. Sinar Wijaya Plywood Industries did a request of Building Right to the land that was occupied by the community of Woriasi tribe. How the application procedure of the customary land Woriasi tribe relinquishment as the grants of Building Right to legal agency that is PT. Sinar Wijaya Plywood Industries already gives the legal certainty.The data collected from the field was analyzed descriptively qualitative where the primer and secondary data. The conclusion from the customary land Woriasi tribe relinquishment happened before between custom society with legal agency was agreed because discussion and fulfilment of the application of regulatory requirements Building Right. The state that holds the highest power could regulate the use of land also could be considered the aspects of the proposal that delivered and could be responsible by the applicant so appointed Decree of the Ministry of Agrarian and Spatial Planning / Head of the National Land Agency Number 34 / HGB / KEM / ATR / BPN / VI / 2019 is legality of the process of Building Right application.